MOTIF, FUNGSI, DAN KEARIFAN LOKAL BEBERAPA LEGENDA DI KOTA SAWAHLUNTO - Arriyanti Usman (tuahtalino, 2020)
This paper describes and examines about the motives, functions, and local wisdom of some legends in Sawahlunto. This research is a qualitative research using comparative descriptive method. To see the motives of folklore, the author applies a group of motives formulated by Stith Thompson. There are several formulas of folklore motives, among them 1) motives of animal, 2) motives of taboos, 3) motives of fraud, 4) motives of community , 5) motives of character, and others. The social functions revealed in the discussion, among others folklore that serves as a means to educate and learn about life, a means to inherit or continue the tradition of a nation in a positive sense, a means to give social sanctions for people to behave well or punish, the means to praise the kings, leaders, people who are considered as a holy one or sacred, and others. The value of local wisdom revealed in the folklore, among them any crime must be punished, there are substances other than humans, nature can be a source of inspiration to give a name to a region, and others.